Juvenile Nasopharyngeal Angiofibroma with Intracranial Extension : A Case Report (IAHS Medical Journal, 2022)
Background: Juvenile Nasopharyngeal Angiofibroma (JNA) is a benign but aggressive neoplasm, shows propensity for destructive local spread and often extends to the base of the skull and into the cranium. It generally presents as painless, unilateral or bilateral nasal obstruction with or without epistaxis. Diagnosis is aided by clinical examination and specialized imaging techniques such as CT scan & MRI, and confirmed by excision and histopathology. In this article, we aimed to present the diagnostic dilemma of an invasive nasopharyngeal mass with massive extension.Case Report : A 16-year-old male presented with a bilateral nasal obstruction, recurrent epistaxis, hearing and breathing difficulties. After total clinical, radiological and histopathological evaluation it was diagnosed as juvenile nasopharyngeal angiofibroma.Conclusion: The approach to its diagnosis and management was a combined multi-disciplinary effort of otorhinolaryngology, radiology and pathology.IAHS Medical Journal Vol 4(1), June 2021; 74-77